The Leading World's Most Innovative Universities - AI-Youbi, Abdulrahman Obaid; Zahed, Adnan Hamza Mohammad; Nahas, Mahmoud Nadim; Hegazy, Ahmad Abousree (Springer International Publishing : Imprint: Springer, 2021)
This open access book is unique in its contents. No other title in the book market has tackled this important subject. It introduces innovation as a way of practice for world-class universities. It, then, discusses the criteria for being innovative in the academic world. The book selects some of the top innovative world-class universities to study the factors that qualified them to be innovative, so that any other university can follow their steps to become innovative. The final chapter of the book presents some recommendations in this regard.